Parenting anxious kids : understanding anxiety in children by age and stage - Galanti, Regine (Sourcebooks, 2024)
"Most parents are not child psychologists and that's why it can be hard to discern what are normal childhood anxieties and what is more problematic. However, even with childhood anxieties, parents can learn how to raise resilient, independent, and healthy children with the help of licensed clinical psychologist, Regine Galanti, PhD. Galanti offers a research-based, practical guide for parenting through all ages and stages with strategies to help build coping skills from toddlerhood through young adulthood. Packed with resources for parents, this book includes guides to childhood anxiety based on developmental stages, assessments for parents, cognitive behavioral therapy skills for both parents and kids, and much more"--